2001
DOI: 10.1046/j.1365-2524.2001.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Users’ views on hospital and home care for acute illness in childhood

Abstract: This mainly qualitative study compared 40 families' experience of hospital and home care. This is one aspect of a randomised, controlled trial, which aimed to evaluate the clinical and cost effectiveness of a paediatric hospital at home service (HAH) for acute illness in children. This paper builds upon previous work that has aimed to examine parents' and children's views as service users. Forty families from a larger sample population took part in structured interviews. Eleven children aged 5 to 12 years took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 17 publications
3
39
1
3
Order By: Relevance
“…Studies of paediatric nurse home-visiting services have found a variable impact on inpatient service utilisation with some studies showing no change in general readmission rates 2 and others showing a reduction for specific diagnosis related groups such as asthma. 12 Importantly, one consistent finding in the literature has been parental preference for such services, 13,14 which is in keeping with our experience. One limitation to our survey is that it may be difficult for families who are from culturally and linguistically different backgrounds, or who are illiterate, to respond.…”
Section: Constraintssupporting
confidence: 84%
“…Studies of paediatric nurse home-visiting services have found a variable impact on inpatient service utilisation with some studies showing no change in general readmission rates 2 and others showing a reduction for specific diagnosis related groups such as asthma. 12 Importantly, one consistent finding in the literature has been parental preference for such services, 13,14 which is in keeping with our experience. One limitation to our survey is that it may be difficult for families who are from culturally and linguistically different backgrounds, or who are illiterate, to respond.…”
Section: Constraintssupporting
confidence: 84%
“…At home, they continued with their usual tasks and were satisfied actively participating in their child's care, learning how to recognize signals and symptoms that required intervention, document children's progress, monitor temperature, administer medication and inhalation (25) .…”
Section: Benefits Of Children's Early Hospital Dischargementioning
confidence: 99%
“…Children themselves affirmed they would rather remain at home than in the hospital, saying that they felt safer, and could play with their own toys. Parents affirmed they had more freedom, and comfort, received individual attention from the nursing team, continued the family's normal life, decreased financial costs, observed that children were better recovering at home, and that the disease was not so serious (25) .…”
Section: Benefits Of Children's Early Hospital Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows CCN services provide health care at home for a wide range of needs, 9 including acute (for example, see [16][17][18][19][20] ) long-term and complex (for example, see [21][22][23][24] ) and end of life. 9 They undertake a range of clinical care activities (for example, home chemotherapy regimens) and, depending on skill mix, may be able to offer advanced nurse practice, such as assessing and prescribing.…”
Section: Realising Children's Health Care 'Closer To Home' In Practicementioning
confidence: 99%